GR_GERICHTE ZF 2004 92 vom 8. Februar 2005 , Forderung (Prozessentschädigung) - GR Gerichte (2005)
Forderung (aktienrechtliche Verantwortlichkeit/Organstellung/Schaden/Kausalität/Schadensnachweis) | Leitentscheid, publiziert als PKG 2005 4\x3Cbr\x3E | OR AG/andere Handelsgesellschaft/Genossenschaft